2016
DOI: 10.1016/j.neurobiolaging.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Loss of auditory sensitivity from inner hair cell synaptopathy can be centrally compensated in the young but not old brain

Abstract: A dramatic shift in societal demographics will lead to rapid growth in the number of older people with hearing deficits. Poorer performance in suprathreshold speech understanding and temporal processing with age has been previously linked with progressing inner hair cell (IHC) synaptopathy that precedes age-dependent elevation of auditory thresholds. We compared central sound responsiveness after acoustic trauma in young, middle-aged, and older rats. We demonstrate that IHC synaptopathy progresses from middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
111
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 81 publications
15
111
2
1
Order By: Relevance
“…Peripheral activation in the present study was measured using ABR wave I, which is proportional to the number of intact IHC-AN synapses [Chambers et al, 2016, Möhrle et al, 2016, Sergeyenko et al, 2013]. Comparable wave I amplitudes therefore suggest comparable aggregate numbers of IHC-AN synapses synchronously and transiently activated by the tone ABR stimuli used.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Peripheral activation in the present study was measured using ABR wave I, which is proportional to the number of intact IHC-AN synapses [Chambers et al, 2016, Möhrle et al, 2016, Sergeyenko et al, 2013]. Comparable wave I amplitudes therefore suggest comparable aggregate numbers of IHC-AN synapses synchronously and transiently activated by the tone ABR stimuli used.…”
Section: Discussionmentioning
confidence: 90%
“…Comparable wave I amplitudes therefore suggest comparable aggregate numbers of IHC-AN synapses synchronously and transiently activated by the tone ABR stimuli used. Although IHC-AN synapses are not required for some degrees of sound detection and discrimination [Chambers et al, 2016, Wang et al, 1997], their function is correlated with rapid temporal processing [Chambers et al, 2016, Möhrle et al, 2016]. The present study used supra-threshold sound levels (40–50 dB SL) that would drive activation of high and low spontaneous rate auditory nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, an increasing number of studies have now demonstrated that the counting of IHC ribbons after hearing loss, for example, in aged specimens [62,64] , or after an acoustic trauma [22,31,32,61,75,76] , or after intake of aminoglycoside [77,78] , can be a first indication of the loss of IHC synapses and AN integrity, independent of (elevated) hearing thresholds.…”
Section: Molecular Biomarker For Dissection Of the Ihc Phenotype And mentioning
confidence: 90%
“…Low sound pressure levels first activate the high-SR fibers, meaning that intact CAP thresholds can provide an estimate about intact high-SR fibers. On the flip side, increasing sound pressure in a row drives the medium-and low-SR fibers, the latter being the most vulnerable to noise [61][62][63][64][65] but which do not contribute to CAP responses at threshold [66] .…”
Section: The Compound Ap Of the Auditory Nerve As A Biomarker To Detementioning
confidence: 99%
See 1 more Smart Citation